Public communication of COVID-19 in the southeastern region of Brazil (Research, Society and Development, 2023)
Objective: To analyze the types and sources of up-to-date information on COVID-19 among the residents of southeastern region of Brazil. Methodology: Cross-sectional, descriptive study, carried out with a sample of 2,477 participants residing in the southeastern region of Brazil. Data collection took place in the period between July 7th and August 28th, 2020. The instrument was made available online, through the Google Forms application. Results: There was a predominance of females (70.2%) and higher education (71.4%). The sources of up-to-date information on COVID-19 most cited by study participants were neighbors and friends (94%) and that disease prevention and control measures were the type of information most received by participants in this study (93%). It was also found that female participants with higher education received more different types of information and updated sources about COVID-19. Conclusion: The results point to a possible ineffectiveness in public communication by authorities, specialists and health professionals, suggesting that official communication channels were not the most used by the study population.